ANALISIS KEMAMPUAN LITERASI DIGITAL MAHASISWA DALAM PEMBELAJARAN DARING KOLABORATIF PADA MATA KULIAH KONSEP DASAR IPS - Zakiyah Ismuwardani; Frumenius B Dole; Herisa Hardiyanti Sholeha (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The aim of this research is to analyze and describe students' digital literacy abilities in collaborative online learning. This research uses qualitative methods with data collection in the form of observations, interviews and documentation studies. The sample in this research was first semester students who took part in a collaborative online learning program with basic social studies concepts courses, consisting of PGSD students at the Institut Pendidikan dan Bahasa Invada Cirebon, as well as PGSD students at the Universitas Flores. The data analysis technique in this research uses qualitative descriptive analysis; the Miles & Huberman model includes data collection, reduction, presentation and drawing conclusions. The research results show that first semester students already have good digital literacy skills. It can be seen from the results of data analysis carried out by researchers in the form of interviews and documentation studies during the implementation of collaborative online learning.